2019
DOI: 10.5032/jae.2019.03128
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Challenges Pre-service Teachers Encountered When Teaching Curriculum for Agricultural Science Education (CASE) Coursework during Student Teaching

Abstract: Student teaching is the capstone experience in an agricultural teacher preparation program (Edgar, Roberts, & Murphy, 2011). During student teaching, pre-service teachers work with cooperating teachers to learn to effectively deliver instruction (Feiman-Nemser & Buchmann, 1987) on topics such as agriscience, agricultural mechanics, horticultural science, and so forth, to secondary students. School-based agricultural education (SBAE) also includes instruction in applied academic content (Stubbs & Myers, 2015). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The challenges these teachers expressed (e.g., students' reluctance to engage, cost of materials, etc.) were consistent with other studies that focused on the use of CASE in SBAE settings (Lambert et al, 2014;Wells et al, 2019). Particular to the CASE MSA curriculum, however, the tailoring of the small gas engines unit was so particular that teachers who did not have the small gas engines originally used in the CASE MSA curriculum materials were forced to augment their curricula and adjust the depth of the CASE MSA experience for their students.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 83%
“…The challenges these teachers expressed (e.g., students' reluctance to engage, cost of materials, etc.) were consistent with other studies that focused on the use of CASE in SBAE settings (Lambert et al, 2014;Wells et al, 2019). Particular to the CASE MSA curriculum, however, the tailoring of the small gas engines unit was so particular that teachers who did not have the small gas engines originally used in the CASE MSA curriculum materials were forced to augment their curricula and adjust the depth of the CASE MSA experience for their students.…”
Section: Conclusion Discussion and Recommendationssupporting
confidence: 83%
“…Another review of the literature showed that dominant problems of pre-service teachers are on the learning environment, cooperating teachers, peers, students, assigned tasks [8], [9], lack of school engagement [5], language barrier [10], and resources [7]. Such difficulties in various aspects of field observation may block the enhancement of field experiences like practicum.…”
Section: Difficulties Of Pre-service Teachersmentioning
confidence: 99%
“…This study addresses Research Priority Area Five: Efficient and effective agricultural education programs within the American Association for Agricultural Education's National Research Agenda (Roberts et al, 2016). Researchers have conducted several studies on CASE, including the challenges of preservice implementation (Wells et al, 2019), student development of critical thinking, task value, autonomy, and science lab self-efficacy (Velez et al, 2015), science teaching efficacy (Ulmer et al, 2013), teachers' intentions to integrate science into agriculture classrooms (Pauley et al, 2019). However, limited research has been done on preservice teachers attending CASE institutes or what skills are gained through CASE professional development.…”
Section: Purpose and Objectivesmentioning
confidence: 99%